Genetic improvement of Trichoderma ability to induce systemic resistance - Ciliento R; Woo S L; Di Benedetto P; Ruocco M; Scala F; Soriente I; Ferraioli S; Brunner K; Zeilinger S; Mach R L; Lorito M (浙江大学学报. 农业与生命科学版, 2004)
The beneficial applications of Trichoderma spp. in agriculture include not only the control of plant pathogens, but also the improvement of plant growth, micronutrient availability, and plant tolerance to abiotic stress. In addition, it has been suggested that these fungi are able to increase plant disease resistance by activating induced systemic resistance (ISR). The mode of action of these beneficial fungi in the Trichoderma-plant-pathogen interaction are many, complex and not completely understood. Numerous lytic enzymes have been characterized, the encoding genes (ech42 gluc78, nag1 from T. atroviride strain P1) cloned, and their role in biocontrol demonstrated. The corresponding biocontrol-related inducible promoters have been used in a reporter system based on the Aspergillus niger glucose oxidase gene (goxA) to monitor biocontrol activity. Glucose oxidase catalyzes the oxygen-dependent oxidation of D-glucose to D-glucono-1, 5-lactone and hydrogen peroxide; this latter compound is known to have an antifungal effect and activate the plant defence cascade, thus increasing resistance to pathogen attack. T. atroviride P1 transformants with various promoters gox were tested as seed coating treatments on bean seeds planted in soil infested with a soilborne fungal pathogen. Successively, the emergent leaves were inoculated with a foliar pathogen to determine the effect of the GOX transformants on biocontrol and resistance to pathogen attack. Inoculations with the P1-GOX transformants not only reduced disease symptoms caused by a soil pathogen, but also the lesions of various foliar pathogens applied far from the Trichoderma colonization, thus activating ISR. A similar approach is being use to genetically improve T. harzianum T22, a rhizosphere competent and commercially marketed strain not transformed yet, by using four different gox gene constructs under the control of constitutive and inducible promoters. Plasmids have been introduced in Trichoderma by protoplasts co-transformation. hygromicin resistant progeny selected, and mitotically stable transformants analysed to confirm the presence of the novel enzyme activity. Progenies are being tested for biocontrol ISR inducing activity.